2017
DOI: 10.1103/physrevd.96.084037
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals criticality in AdS black holes: A phenomenological study

Abstract: AdS black holes exhibit van der Waals type phase transition. In the extended phase-space formalism, the critical exponents for any spacetime metric are identical to the standard ones. Motivated by this fact, we give a general expression for the Helmholtz free energy near the critical point which correctly reproduces these exponents. The idea is similar to the Landau model which gives a phenomenological description of the usual second order phase transition. Here two main inputs are taken into account for the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 67 publications
(106 reference statements)
2
39
0
Order By: Relevance
“…It was indeed shown that in this alternative phase space, phase transition and critical behavior of RN-AdS black hole, in four dimensions, occur in the Q 2 -Ψ plane, where relevant response function clearly signifies stable and unstable region [1]. Remarkably, in this viewpoint, the small-large black hole phase transition is quite similar to the Van der Waals liquid-gas system and belongs to the same universality class in contrast with previous study of [16]. Additionally, it would be interesting to study the universality class and critical properties for any AdS black hole in an alternative phase space where the cosmological constant (Λ) is taken to be constant.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…It was indeed shown that in this alternative phase space, phase transition and critical behavior of RN-AdS black hole, in four dimensions, occur in the Q 2 -Ψ plane, where relevant response function clearly signifies stable and unstable region [1]. Remarkably, in this viewpoint, the small-large black hole phase transition is quite similar to the Van der Waals liquid-gas system and belongs to the same universality class in contrast with previous study of [16]. Additionally, it would be interesting to study the universality class and critical properties for any AdS black hole in an alternative phase space where the cosmological constant (Λ) is taken to be constant.…”
Section: Introductionmentioning
confidence: 52%
“…In this view, the thermodynamic behavior of AdS black hole is analyzed in a thermodynamics phase space. The critical point and associated critical exponents in a phase space of black hole have been studied in a general way [16]. It was found that the values of critical exponents differ from those of the Van der Waals phase transition [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For non-extremal black holes, there are two major approaches of studying the phase transition of black hole-one approach deals with the divergence of heat capacity and inverse of isothermal compressibility [31][32][33][34][35][36][37][38]. The other approach [39][40][41][42] is for the black holes in the AdS background, in which the cosmological constant is treated as the thermodynamic pressure. The latter approach exactly resembles the phase transition of the van der Waals fluid system.…”
Section: Gtd In Extremal Phase Transitionmentioning
confidence: 99%
“…Although the analysis apparently is intriguing, its main limitation was the lack of a proper canonical definition of P and V variables. Later on, when the cosmological constant was taken as a variable and included in the extended version of first law [13][14][15][16][17] (also see our work [65], where the first law in the extended phase space has been obtained from the conserved Noether current following Wald's method), the canonical definition of P and V was provided and was shown that the van der Waals P − V criticality exists in black hole spacetime [18,19,74,75] and at the critical point, two independent conditions coincide i.e.…”
Section: Thermodynamic Geometry In a Legendre Invariant Way: A Brief mentioning
confidence: 99%